AhR regulation of amyloid beta-induced inflammation in astrocyte cells - Ojo, Emmanuel; Adu, Temitope; Aameri, Raheem F. H. AI; Tischkau, Shelley A. (Frontiers in Cellular Neuroscience, 2025)
IntroductionAmyloid beta (Aβ) plaques, tau tangles, and neuroinflammation are common features present in Alzheimer’s Disease (AD), and glial cells are essential mediators of the inflammatory reaction. Aryl hydrocarbon receptor (AhR), a transcription factor engaged in regulation of immune function, may be involved in the pathogenesis of AD, through modulation of neuroinflammation. This study explores how AhR affects astrocyte function in response to inflammatory stimuli, with emphasis on Aβ.Methods and ResultsIn primary hippocampal astrocyte cultures from wild type (WT, C57BL6/J) or AhR germline knockout (AhRKO) mice, pretreatment with the AhR agonist, 6-Formylindolo[3,2-b] carbazole (FICZ), attenuated Aβ-induction of reactive astrocyte development, characterized by decreased astrocyte complement C3 expression and decreased proinflammatory cytokine release. In addition, Aβ exposure exacerbated TNF-a cytokine release and increased GFAP immunoreactivity in astrocytes derived from AhRKO mice. In response to Aβ injection into the mouse hippocampus in vivo, AhRKO mice demonstrated increased astrocyte hypertrophy, reinforcing AhR function in regulating astrocyte responses to neuroinflammation.DiscussionThese findings suggest that AhR activation in astrocytes attenuates development of the neuroinflammatory state, and identifies AhR as an interesting therapeutic target to mitigate neuroinflammation and the progression of AD.